Development of industrial enterprises due to organizational changes - Malevskyy, Eduard (Skhid, 2020)
The paper establishes the main provisions for the construction of organizational support for change management in machine-building enterprises, which should be based on regulations and internal regulations of the organization. It is proved that organizational changes are characterized by a complex nature, when changes in individual processes require appropriate adjustment and modernization of the organizational structure of the industrial enterprise. Also, the need for organizational change is often a consequence of changes in the technological and production sphere of the industrial enterprise, when the development of new technologies, transition to production of new or improved products, entry into new markets, etc. is impossible without appropriate organizational change.